The The Gender Power in Managerial Entrepreneurship and Corporate Social Responsibility Relationships - Evan Nicholas Diharjo; Riesanti Edie wijaya (Journal of Economics, Business, and Government Challenges, 2022)
The The Gender Power in Managerial Entrepreneurship and Corporate Social Responsibility Relationships